A Foresight Study on the Adoption of Assistive Technology among Disabled People - Salim, Siti Aisyah; Razali, Nursyahidah (Research in Management of Technology and Business, 2022)
The improvement of assistive technology has the potential to help more user especially with special need to carry out their daily activities. Though assistive technology has helped people with the impairment, most of them could not realize the benefits as they don’t have the knowledge to use it. Therefore, this study aims to identify key drivers that influence disable people to adopt assistive technologies and among disabled people and to determine the future trend of assistive technologies among disabled people for disabled people Malaysia. A mixed method approach which consists of STEEPV and quantitative study will be used in this research. Ten merged key drivers and issues had been identified. While, the impact-uncertainty analysis approach had been used to identify the future trends of Assistive Technology adoption. 384 questionnaires had been distributed to the people at who are the disabled people who had registered as OKU (Orang Kurang Upaya) under Malaysian welfare department and the people who support and engage with him or her on a daily basis with response rate 14.4%. This study found that enhance user’s performance and ease in movement and mobility had the highest impact and uncertainty. Four scenarios were proposed at the end of the study. The four scenarios were quality standards and quality assurance systems, expectations and control over surroundings, promotes acquisition of literacy and frustration and anxiousness.